Assessment of pharmacokinetic parameters of lupeol in Ficus religiosa L. extract after oral administration of suspension and solid lipid nanoparticles to Wistar rats - Priyanka K.; Kosuru R.; Sharma R.P.; Sahu P.L.; Singh S. (My University, 2025)
In spite of wide applications of herbal drugs as phytochemicals or extracts, their application is limited because of their poor bioavailability. The aim of the present work was to enhance the poor bioavailability of lupeol present in Ficus religiosa L. extract through solid lipid nanoparticles (SLN). Ficus religiosa L. extract loaded SLN were prepared and administered orally to male Wistar rats for bioavailability studies. Developed SLN were characterized for particle size, PDI, zeta potential, entrapment efficiency, in vitro drug release and stability studies. Further, interaction studies were carried out. Bioavailability studies were performed for Ficus religiosa L. extract in suspension form and SLN form. AUC of lupeol was increased by 9.2 - folds in rats treated with SLN compared to suspension. Also, Cmax of lupeol was increased by 3.9 - folds in rats treated with SLN compared to suspension. t1/2 of lupeol was found to be 7.3 ± 1.0 h in suspension and 15.3 ± 1.3 h in SLN. SLN enhanced AUC and Cmax and prolonged t1/2 of lupeol in Ficus religiosa L. extract which in turn may lead to dose reduction, prolonged duration of action and also enhanced therapeutic efficacy. © 2017 Elsevier B.V.